Effects of novel and historic predator urines on semi-wild western grey kangaroos - Parsons, Michael; Lamont, Byron; Kovacs, B.; Davies, Stephen (Wildlife Society, 2007)
Classic studies in fear ecology have been inconclusive regarding whether predator waste products repel herbivores and whether the deterrent effect, if any, is based on repulsion or fear. Other studies imply that the predator must have co-evolved with prey to maximize the efficacy of response. We used chemosensory cues from the urine of native and nonnative canines to manipulate the behavior of the western grey kangaroo (Macropus fuliginosus). One-choice feeding trials were located along a distance gradient, and administered to 28 free-ranging, semi-wild, western grey kangaroos. Foods closer to the chemical source (within 12 m) were less likely to be eaten than those further from the source when the urine came from a native predator, the dingo (Canis dingo). Flight behavior was more likely to be observed on occasions when the dingo urine had been presented. A lesser effect occurred (to within 6 m) when urine was presented from the nonnative canid (coyote [Canis latrans]), while the flight behavior occurred once. Neither human urine, nor tap-water control, had any effect. We offer the first evidence that native predator-based chemical cues affect patch selection, while increasing fear, for this herbivore.